Implications of Educational Digital Media Scratch Games in Social Sciences Learning for Primary School Student Motivation - Faddyasinta Sahnabila Rahmadika; Rachma Nurfitria; Yosi Anggia Margaret Tambunan; Nurdiansyah, Nurdiansyah (Penerbit Hellow Pustaka, 2024)
Effective education is the key to developing students to face life's challenges. Learning motivation serves as a push for students to be active in their learning activities, greatly influenced by the level of effort and abilities they possess. Students with stronger learning motivation tend to be more diligent and always pay attention to teacher instructions during the learning process. Student learning motivation can be honed through educational games. Digital media such as Scratch has attracted the attention of educators as an innovative tool to enhance learning in various fields, including Social Sciences. This research uses a qualitative approach to understand the implications of Scratch in Social Sciences learning. Scratch, as a visual programming language, facilitates various creative projects. Its use in elementary schools has shown increased student motivation, including engagement, creativity, and collaboration. With proper implementation, Scratch can reinforce cognitive learning, programming skills, and collaboration. Its positive implications include increasing interest in learning, student participation, and digital competence. The use of Scratch has great potential to enhance student motivation and develop their various competencies. In the educational context, Scratch is a powerful tool to facilitate enjoyable and meaningful learning for students. For successful implementation, appropriate steps are needed, including platform introduction, understanding basic programming concepts, and providing feedback. In conclusion, Scratch can be an effective tool in enhancing Social Sciences learning in elementary schools, with a positive impact on student motivation and competency development.